Economic Aspects of Pandan Fiber Furniture from the Area of Sustainable Design Philosoph - F Maharlika (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
In terms of sustainable design philosophy, the goal of this study is to describe the fulfillment of economic principles through furniture made from Pandanus fiber. Respecting the needs of current and future generations, energy efficiency, cost-effective and sustainable solutions, and easy product maintenance are all areas of sustainable design philosophy. The qualitative research method was used. The findings of this study show that chair furniture made from Pandan fiber satisfies both economic and philosophical principles of sustainable design, because the manufacturing and processing of waste do not incur high costs due to the lack of heavy equipment, machinery, or chemicals used in the management process. On the contrary, the resulting product is strong and long-lasting.